Biuletyn Informacyjny . no. 47, 1981 - NSZZ "Solidarność" Stocznia im. Komuny Paryskiej, [ed. Czesław Richert, Mariusz Różański] (KZ NSZZ Stocznia Gdyńska, 1981)
Creation and circulation: In early 1989 interrim Solidarity organization in the Komuna Paryska Shipyard published a number of issues of the still illegal publication